Effective Training Factors for Competency of Demolition Operatives in Malaysia - Ganjbakhsh, Hamed; Abdullah, Arham Bin; Sadi, Mohammadali Kazerooni; Yadollahi, Mohammadreza (International Journal of Economics and Financial Issues, 2015)
Recently, technology advancement influenced almost every field of life, brings new tools and techniques to reduce human effort and risk involved. Similar in the case of demolition industry, technology changed the demolition procedures significantly. Most of the countries are opting new techniques for demolition operatives, which ultimately reduce the risk involved the demolishing process. Effective competency based training modules has been adopted by the many countries to develop the demolition operatives skills, so the health and safety measure could be increased and also reduce the environmental impacts of the process. Malaysia has demolition procedure but unfortunately, the standards are not updated as compare to the other countries like UK, Australia etc., this enhances the element of the risk in demolition procedures. Current study has examined the factors that influence the demolition operative competency in Malaysian demolition industry. Results indicated that technical competency, risk management, health and safety and the environmental protection practices are the basic practices need for the demolition operatives. Keywords: Technology Advancement; Demolition; Competency; Environmental Protection JEL Classifications: M000